The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.7759/cureus.51302
|View full text |Cite
|
Sign up to set email alerts
|

Gummy Smile Prevalence Among Ha’il City Female Young Adults and Its Impact on Quality of Life: A Cross-Sectional Study

Arwa A Al Sayed,
Bodor Z Alshammari,
Abdullah R Alshammari
et al.

Abstract: Background: Gummy smile (GS) has a direct effect on individuals, especially among young adults, because of its association with smile avoidance. The younger populations are sensitive about their smiles and prefer aesthetic, beautiful smiles, a lack of which can negatively impact their quality of life. Objectives: This study aims to measure the GS prevalence among young adults aged 16 to 18 attending high schools in Ha’il City, Saudi Arabia, evaluating oral health related to quality of life (OHQoL) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Previous studies conducted in different countries of the world identified perceived dental and orthodontic needs, i.e., problems in the alignment of teeth, skeletal and functional issues, as the main factor affecting parents’ attitude towards seeking early orthodontic interventions for their children [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted in different countries of the world identified perceived dental and orthodontic needs, i.e., problems in the alignment of teeth, skeletal and functional issues, as the main factor affecting parents’ attitude towards seeking early orthodontic interventions for their children [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%